Tourist perception and behaviour towards public mural art installation in Georgetown Heritage District, Malaysia - Mahmound, Elham Karimian (2016)
Public Mural Art Installation (PMAI) is normally planned and executed in the urban open space and accessible to the public for tourism activities. In recent years, public mural art installation (PMAI) has increasingly expanded in Penang Georgetown Heritage District (PGHD) which enhance the local identity towards tourists. Despite the expansion, it seems that most tourists have difficulties in understanding the PMAI and this is due to its inefficient planning and design in the heritage district of Georgetown. There is an imperative need to ascertain to what extent has the PMAI facilitates the identity of PGHD by understanding the tourists’ perception and behaviours and during their engagement with PMAI in heritage district. Moreover, applying PMAI as modern design characteristics may not have a positive impact on the manner the PMAI enhance the place identity of PGHD. The mixed methodologies selected are a non-participant observation and distributed random survey questionnaires (SQ) amongst tourists in the PGAD. Subsequently, physical and statistical analysis SPSS were selected to analyse the collected data. The study demonstrates that the level of perception and satisfaction of PMAInin terms of enhancing the identity of the place amongst tourists in PGHD isnsatisfactory. As the result of the analysis, it is clear that most tourists believed applying PMAI as a modern installation in the heritage district of Georgetown has managed to increase local identity and its effectiveness can be further enhanced with the addition of the local socio-cultural characteristics. This study contributes to the improvement of current PMAI design qualities in PGHD to enhance the place identity. It will also assist in formulating appropriate policy and guidelines in constructing the PMAI in heritage districts globally.